Kajian Pengaruh Struktur Organisasi, Komitmen Karyawan, dan Pemahaman Tujuan Operasi terhadap Penerapan Total Production Maintanance (TPM) serta Implikasinya pada Kinerja Karyawan - Sutrisno Sutrisno (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
The purpose of this study to identify, analyze and assess: the influence of organizational structure,employee commitment and understanding of the purpose of operating the company's total productivemaintenance slate pencil group, and total productive maintenance influence on employee performance of thecompany's operations slate pencil group. This research is descriptive and verification. The populations in thisstudy were employees of the company's operations slate pencil, while the unit observer is a staff of about1,868 people with a sample of 317 employees. Analysis of the data using Path Analysis. The results of this study showed that there is a significant effect partially, either directly or indirectlybetween the variables of organizational structure, employee commitment and understanding of the operationalobjectives of the implementation of total productive maintenance. Contributions amount of influence on theorganizational structure of the implementation of total productive maintenance in second place. There is a simultaneous effect between organizational structure, employee commitment andunderstanding of the operational objectives of the implementation of total productive maintenance. Operationobjective understanding of the application of total productive maintenance have the most influence among thethree variables studied and followed by the organizational structure and employee commitment. Influence simultaneously or jointly variable organizational structure, employee commitment, andunderstanding operating purposes of the application of total productive maintenance at 0.616. While theremaining 38.4% is influenced by other variables outside the model is not examined. There is the influence ofthe implementation of total productive maintenance on employee performance of operations with the amountof influence of 73,2% (seventy-three point two) percent. Thus the effect of the implementation of totalproductive maintenance on employee performance of operations is very significant.